E. DELGADO ORUSCO y J. VIVER - El Faro / The Lighthouse - López-Bahut, Emma (ZARCH, 2017)
Eduardo Delgado Orusco y Javier ViverEl Faro / The LighthouseRU books, Málaga, 2016, 132 páginas.Idiomas: castellano/ inglés. 21 x 21 cm. Cubierta blanda. 15 €. ISBN: 978-84-944786-1-1